The development of school well-being in secondary school: High academic buoyancy and supportive class- and school climate as buffers. (February 2021) - Hoferichter, Frances; Hirvonen, Riikka; Kiuru, Noona
Abstract: Students experience increasing pressure to perform well and worry about their academic performance before critical school transitions. These challenges may compromise students' school well-being. Drawing on the Model of Personality and Affect for Education (Matthews et al., 2005) as well as on the Conservation of Resources Theory (Hobfoll, 1989), we investigated the buffering role of high academic buoyancy and supportive class- and school climate against decreases in school well-being (i.e., school-related stress, anti-school attitude, and satisfaction with school) among Finnish lower secondary school students ( N  = 1024) from grades seven to nine. Controlling for gender, fluid intelligence, and parental education, the results of latent structural equation models indicate that academic buoyancy contributed to school satisfaction, while class- and school climate buffered against the increase of anti-school attitude. The study underlines the importance of both personal and contextual factors, contributing differently to students' school well-being. Highlights: High academic buoyancy buffers the relationship of school-related stress from grade seven to nine among Finnish students. High academic buoyancy contributes to school satisfaction from grade seven to nine among Finnish students. A positive class- and school climate protect students against the increase of anti-school attitude from grade seven to nine. Academic buoyancy and class- and school climate contribute differently to students' school-related well-being.